Shear strength of thin web – influence of lighting openings and diagonal tension. Issue 1 (2nd January 2016) - Horák, Marek; Píštěk, Antonín
Abstract: This article provides information about stress analysis of thin beam webs with and without lighting openings. The study described in this paper was carried out in order to investigate the influence of circular lighting openings in planar webs on critical web shear force, distribution of transverse web deformations, and also strain and stress distribution in the web plate. The main goal was to compare pre- and post-buckling behaviour of a thin web with and without lighting openings under shear load. The procedure was as follows: first of all, seven specimens – beams with a different combination of parameters (web thickness, opening size and web dimension) were calculated using available analytical methods; secondly, the same specimens were produced and tested up to load near failure; thirdly, these specimens were analysed using the Finite element method; finally, the tests results were compared with results of numerical simulations.